A mathematical model for chronic wounds - Avner Friedman; Chuan Xue (Mathematical Biosciences and Engineering)
Chronic wounds are often associated with ischemic conditions whereby the blood vascular system is damaged. A mathematical model which accounts for these conditions is developed and computational results are described in the two-dimensional radially symmetric case. Preliminary results for the three-dimensional axially symmetric case are also included.